GAMBARAN FAKTOR YANG MEMPENGARUHI PILIHAN KONSUMEN TERHADAP PEMBELIAN OBAT BEBAS DI APOTEK “X” SURAKARTA - Manek, Yohanes Stephen; Ariastuti, Reni; Sakti Pambudi, Risma (FARMESTRA: Jurnal Pelayanan dan Teknologi Kefarmasian Indonesia, 2023)
Over the counter drugs are drugs that can be purchased freely at drug stores such as pharmacies, supermarkets, and drug stores. Drug selection can be influenced by several factors such as drug effectiveness, price, packaging design, safety, brand, promotions and recommendations from other parties. People often get drug information through other and print or electronic media advertisements, which are the most impressive types of information and are easy to understand. This research aims to determine factors that influence consumer choices regarding purchasing over-the-counter drugs at drug store "X" in Surakarta. The research used a cross sectional descriptive method. Primary data was collected through direct observation regarding the description of factors that influence the purchase of over-the-counter drugs without a doctor's prescription at the drugstore. Data was taken from 100 consumer respondents from an "X" drug store in Surakarta. Research data was processed using the Microsoft Excel application. The results show that the factors that influence consumer choices in purchasing over thecounter drugs at drug store "X" Surakarta is the effectiveness at 74.80%, safety at 73.88%, packaging design at 74.2 %, price at 74.4%, brand at 74.95%, promotion at a 73.10% and recommendation from other parties at 70.2%. Based on the results, it can be concluded that the biggest factor influencing consumers in choosing drugs at the drug store "X" Surakarta is the brand factor with an average of 74.95%.